Energy Spectrum of the ⁸Be Nucleus - Батсайхан, Өсөхбаяр (Scientific transaction of the National University of Mongolia. Physics, 2025)
The ⁸Be nucleus is modeled as an α+α system composed of two alpha clusters. Using the complex scaling method with Buck and Schmid-Wildermuth potentials, we calculated the energy levels and corresponding resonance widths for the states with spin-parity Jπ = 0⁺, 2⁺, 4⁺, 6⁺, 8⁺, and 10⁺. The calculations were performed using Gaussian and harmonic oscillator basis functions. The results are compared with existing theoretical models and experimental data.